"Things Are Different Now But": Older LGBT Adults' Experiences and Unmet Needs in Health Care. (September 2020) - Burton, Candace W.; Lee, Jung-Ah; Waalen, Anders; Gibbs, Lisa M.
Background: Approximately 2.7 million U.S. older adults self-identify as lesbian, gay, bisexual, and transgender (LGBT). Many felt unsafe revealing their sexual orientation until relatively recently, and may still not be "out" to medical providers. The aim of this study was to increase understanding of the experiences and needs of older LGBT adults when accessing care.Method: Individual semistructured interviews were conducted with 10 individuals aged 65 years or older from a local LGBT community. Interviews were audio taped and transcribed verbatim. Transcripts were analyzed via thematic analysis.Results: Major themes were "Outness, " "Things are Different Now, " and "Additional Resources." These describe participant comfort with being "out"; how treatment they received changed over time, and needed services or other options from the community.Conclusion: While many older LGBT adults are accustomed to navigating social mores to avoid negative experiences, nurses as well as other health care providers must be prepared to create trusting relationships with these individuals to provide truly comprehensive care.